Environmental Biocatalysis From Remediation to Waste Valorization - Topakas, Evangelos; Nikodinovic-Runic, Jasmina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue aims to highlight the dual potential of novel biocatalytic processes, where the first part is dedicated to waste valorization for the production of high value products, while the second part is focused on the detoxification of pollutants. Several examples of microbial systems employed for the valorization of waste streams derived by the forest, agricultural, and food industries or the use of whole-cell or enzyme approaches for the removal of nitrogen or dyes from industrial wastewaters are provided. Last but not least, an example of the utilization of polyhydroxyalkanoates (PHAs) was highlighted for the production of fatty acids, which were used for the enzymatic synthesis of sugar esters with antimicrobial properties.